Indonesian Defense Diplomacy Strategy in Post the ATT Enforcement - Rodon Pedrason (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
The goal of this study is to examine the Arms Trade Treaty (ATT) after its coming into effect in Indonesia using a defense diplomacy strategy. The research approach used in this study is descriptive analytic qualitative research. The data gathering approaches employed in this study were interviews and literature reviews. According to the findings of this study, every country has the right to access and develop weapons as well as to protect itself. Indonesia, on the other hand, is outside the ATT system since it has chosen to abstain. According to Article 5 of the ATT, Indonesia is not required to report on the feasibility assessment of the transfer of conventional weapons. Indonesia, on the other hand, can improve the conventional weapons regime and the UNPoA to prevent weapons from being circulated in conflict-prone areas.